Chapter Developments in Wireless Power Transfer Using Solar Energy - Himanshu, Dehra (InTechOpen, 2021)
This chapter presents state-of-the-art and major developments in wireless power transfer using solar energy. The brief state-of-the-art is presented for solar photovoltaic technologies which can be combined with wireless power transfer (WPT) to interact with the ambient solar energy. The main purpose of the solar photovoltaic system is to distribute the collected electrical energy in various small-scale power applications wirelessly. These recent developments give technology based on how to transmit electrical power without any wires, with a small-scale by using solar energy. The power can also be transferred wirelessly through an inductive coupling as an antenna. With this wireless electricity we can charge and make wireless electricity as an input source to electronic equipment such as cellphone, MP3 Player etc. In harvesting energy, technologies of ambient solar radiation like solar photovoltaic, kinetic, thermal or electro-magnetic (EM) energy can be used to recharge the batteries. Radio frequency (RF) harvesting technologies are also popular as they are enormously available in the atmosphere. The energy converted to useful DC energy which can be used to charge electrical devices which need low power consumption. The chapter has also presented a parallel plate photovoltaic amplifier connected to a potentiometer as a Resistance-Capacitance (RC) circuit power amplifier. The effect of inductance and resulting power transfer has been theoretically determined in the RC amplifier circuit. The electrical and thermal properties and measurements from a parallel plate photovoltaic amplifier were collected to analyze the unbalanced power transfer and inductance in a nonlinear RC circuit amplifier using equivalent transfer functions. The concept of Wireless Information and Power Transfer using Electromagnetic and Radio Waves of Solar Energy Spectrum is also briefly outlined.